STRUCTURAL FEATURES OF A CLAY FILM HYBRIDIZED WITH A ZWITTERIONIC MOLECULE AS ANALYZED BY SECOND-HARMONIC GENERATION BEHAVIOR - Ogata Y.; Yamagishi A.; Kawamata J.; Chong C.-H.; Saito G. (My University, 2003)
Hybrid Langmuir-Blodgett (LB) films of a single clay layer and a donor-(π-electron system)-acceptor (Dδ-π-Aδ−) zwitterionic molecule (ind-TCNQ), prepared from 1,3,3-trimethyl-2-methyleneindoline (donor) and 7,7,8,8-tetracyanoquinodimethane (acceptor) were prepared. The characteristics of the electrostatic interaction between the clay layer and the ind-TCNQ molecules were investigated. The amount of ind-TCNQ molecules spread onto the air-water interface was increased systematically so that mono- and multi-layers of the molecules could be formed on the clay layer. The hybrid LB films, which were deposited onto a solid substrate, were characterized by means of UV-vis absorption spectroscopy and optical second-harmonic generation measurement. The amount of ind-TCNQ molecules adsorbed on the clay layer increased with an increase in the amount of ind-TCNQ molecules spread onto the air-water interface. On the other hand, the SHG intensities of the films did not change with the change in amount of ind-TCNQ spread. The results indicate that the electrostatic interaction between the clay layer and the ind-TCNQ molecules operates only in the region where the ind-TCNQ molecules are in direct contact with the clay layer.